Extracting essential oils from wild cress (Lepidium aucheri boiss ) and studying their biological effectiveness - محمد كريدي حسام; ماجد كاظم مريم (University of Thi-Qar Journal of Science, 2016)
The present study amide to extracts the essential oils from Lepidium aucheri boiss ,where it was collectedin March 2015 from the northern of Nasiriyah city and it was classified . it was extracted from plantsby Clevenger’s Apparatus to be finally getting around 26.45g of essential oil of 24Kg plant .Then study thebioactivity of this essential oils ,the extracted essential oils from the plant didn’t showed any toxicity toward the red blood cells. The antibacterial properties was used five types of bacteria, Cram positive strain (Staphylococcus aureus, Streptococcus pyogenes and Enterobacter sp.) and Cram negative strain (Escherichia coli, Pseudomonas aeruginosa),These moleules showed antimicrobial activites against gram negative and gram positive bacterial .The activity of the concentration 100% showed the highest percentage inhibition there are (20mm) towards bacteria Staphylococcus and E.coli bacteria showed less inhibition ratio there are (7mm) at the same concentration .In the test of antifungal properties used four types of fungus which Asperggillus niger and Asperggillus terrus and Asperggillus flavus and Candida albicans .The results showed the highest inhibition of the fungus at concentration 100% towards A.niger where the scale inhibition is 12 mm, while the other fungi have shown high resistance toward all the prepared concentration ,especially C.albicans.